Ameliorative effects of jamun seed and orange peel extracts on microcystin LR induced alterations in calcitonin cells and parathyroid gland of rats. Issue 3 (2nd November 2020) - Srivastava, Babita Deep; Srivastava, Manish; Srivastav, Sunil Kumar; Urata, Makoto; Suzuki, Nobuo; Srivastav, Ajai Kumar
Abstract: This study investigated changes in calcitonin cells (C‐cells) and parathyroid glands (PTG) induced by microcystin LR (MCLR) exposure to rats and evaluated ameliorative effects of jamun ( Syzygium cumini ) seed (JSE) and orange ( Citrus sinensis ) peel (OPE) extracts. Wistar rats were treated as—Group A (control), Group B (MCLR), Group C (MCLR + JSE), Group D (MCLT + OPE), Group E (OPE) and Group F (JSE). Microcystin dose was (10 μg/kg body wt/day whereas OPE and JSE dose was 200 mg/kg body wt/day. Thyroid and PTG were fixed on 15 and 30 days following the treatment. C‐cells of treated rats for 15 days with MCLR; MCLR + JSE and MCLR + OPE exhibit degranulation, mitochondrial swelling and prominent RER. In MCLR treated rats few cells completely lack secretory granules. After 30 days MCLR treatment accumulation of secretory granules and degeneration were noticed in C‐cells. C‐cell nuclear volume (NV) of MCLR, MCLR + JSE and MCLT + OPE treated rats show an increase. In MCLR, MCLR + JSE and MCLR + OPE treated rats PTG exhibit hyperchromatic nuclei, nuclear elongation and increased NV after 15 days. After 30 days MCLR treatment nuclei of PTG become more hyperchromatic, more elongated, show degeneration of nuclei and increase in NV. NV is increased in Group C and Group D. PTG remain unaltered 30 days following treatment with OPE and JSE. Microcystin LR provoke physiological effects on the blood calcium and alterations in C cells and PTG, which cause serious threat to organism. These changes can be protected by JSE and OPE. Abstract : The study describes the protective effects of extracts of jamun ( Syzygium cumini ) seeds and orange ( Citrus sinensis ) peels against microcystin LR induced changes in the calcitonin cells and parathyroid glands of male rats Microcystin LR provoked degranulation, mitochondrial swelling and prominent RER in calcitonin cells of 15 days treated rats. In MCLR treated rats few cells completely lack secretory granules. After 30 days MCLR treatment accumulation of secretory granules and degeneration were noticed in C‐cells. In microcystin treated rats PTG exhibit hyperchromatic nuclei, nuclear elongation and increased NV after 15 days. After 30 days MCLR treatment nuclei of PTG become more hyperchromatic, more elongated, show degeneration of nuclei and increase in NV. Treatment with jamun seed and orange seed extracts ameliorates the effects of microcystin on calcitonin cells and parathyroid glands. Prior to this study no report exists regarding protective effects of extracts of seed of S. cumini (JSE) and peels of C. sinensis (OPE) on calcitonin cells and parathyroid glands induced by microcystin LR.